1982
DOI: 10.1037/0022-3514.42.6.1036
|View full text |Cite
|
Sign up to set email alerts
|

Patient behavior in hospitals: Helplessness, reactance, or both?

Abstract: Forty-eight inpatients hospitalized for 1, 3, or 9 weeks and 24 outpatients were tested on cognitive tasks: poor performance and depressive symptoms increased with length of hospitalization, even as illness resolved. Further, increased hospitalization made patients more susceptible to the debilitating effect of uncontrollable events. Taken together, these results imply that the passive, compliant, and inanimate behavior of the "good patient" may be the result of learned helplessness engendered by hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 13 publications
2
33
1
Order By: Relevance
“…In this context external noise may be a distracting influence which puts excessive strain on a failing attentional mechanism in an anxious person. Prolonged exposure to situations inducing learned helplessness such as admission to hospital (Raps et al 1982) has been shown to increase vulnerability to performance deficits caused by noise. Thus noise may be having a greater effect on the already impaired individual.…”
Section: Negative Affectivity and Greater Reactions To Noisementioning
confidence: 99%
“…In this context external noise may be a distracting influence which puts excessive strain on a failing attentional mechanism in an anxious person. Prolonged exposure to situations inducing learned helplessness such as admission to hospital (Raps et al 1982) has been shown to increase vulnerability to performance deficits caused by noise. Thus noise may be having a greater effect on the already impaired individual.…”
Section: Negative Affectivity and Greater Reactions To Noisementioning
confidence: 99%
“…For instance, the frequent use of complex medical jargon by doctors is often perceived as an indicator of such power differential, which might leave patients without the understandable information regarding their condition and process of recovery (Phillips, 1996). In such situations, research has shown that many patients may experience heightened levels of anxiety since they might feel deprived of the much-needed feelings of control and knowledge about the health and recovery (Raps et al, 1982;Williams & Irurita, 2005). For instance, quantitative research data on a sample of hospitalised women indicate that between 10% and 40% were subjected to stress at times when the hospital staff disregarded their need for communicating adequate comprehensive information about many aspects of their care (Polimeni & Moore, 2002).…”
mentioning
confidence: 98%
“…In general, it is not only the physical suffering and distress that puts the body into a state of continuous stress, but also factors that negatively affect the patient's psychological state (Rattray, Johnston, & Wildsmith, 2005). Factors such as perceived threat to one's life, the uncontrollable and unpredictable nature of one's condition often put hospitalised individuals in a state of apprehension and hopelessness, which can have a considerable effect on their thoughts, emotions and subsequent behaviours (Mishel, 1997;Raps, Peterson, Jonas, & Seligman, 1982;Seeman & Seeman, 1983).…”
mentioning
confidence: 99%
“…When patients are cared for in hospital following, say, elective surgery, cognitive function declines as time passes due to the unempowering effect of having all their needs cared for in a controlled hospital environment. 20 By contrast, empowerment can be increased in long-term residential homes by encouraging the residents to make choices about their own lives. 21 Disease itself is often disempowering.…”
Section: Empowermentmentioning
confidence: 99%